Pengaruh Fasilitas, Persepsi Harga dan Kualitas Pelayanan terhadap Kepuasan Tamu Menginap - Mahendri, Made Dwika; Widani Sugianingrat, Ida Ayu Putu; Gede, I Komang (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The existence of attention and findings regarding facility problems, price perceptions and service quality in an effort to improve and increase guest satisfaction stays in accordance with the objectives of this study to determine the positive and significant effect partially and simultaneously between facilities, price perceptions and service quality on guest satisfaction at Bali Mandira Beach Resort And SPA in Kuta Badung. The population in this study were domestic guests as many as 6,527 people. While the number of samples in this study were 98 overnight guests. The method of determining the sample in this study using purposive sampling. The results showed that facilities, perceived price and service quality had a partial and simultaneous significant effect on guest satisfaction, so the hypothesis stated that facilities, perceived price and service quality had a partial and simultaneous positive and significant effect on guest satisfaction at Bali Mandira. Beach Resort And SPA in Kuta Badung is accepted.